2018
DOI: 10.1186/s12864-018-4747-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of adipose tissues from two fat-tailed sheep breeds reveals key genes involved in fat deposition

Abstract: BackgroundThe level of fat deposition in carcass is a crucial factor influencing meat quality. Guangling Large-Tailed (GLT) and Small-Tailed Han (STH) sheep are important local Chinese fat-tailed breeds that show distinct patterns of fat depots. To gain a better understanding of fat deposition, transcriptome profiles were determined by RNA-sequencing of perirenal, subcutaneous, and tail fat tissues from both the sheep breeds. The common highly expressed genes (co-genes) in all the six tissues, and the genes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 81 publications
5
78
1
2
Order By: Relevance
“…Whether these candidate genes play an important role in lipid deposition remains to be studied [54]. In addition, although various pathways, such as the "Wnt signaling pathway," "MAPK signaling pathway," "AMPK signaling pathway" and "PPAR signaling pathway" were not significantly enriched, they were related to fat development and deposition [56][57][58][59]. Therefore, the differentially expressed lncRNAs involved in the aforementioned pathways may play an important role in the process of lipid deposition and deserve further study.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these candidate genes play an important role in lipid deposition remains to be studied [54]. In addition, although various pathways, such as the "Wnt signaling pathway," "MAPK signaling pathway," "AMPK signaling pathway" and "PPAR signaling pathway" were not significantly enriched, they were related to fat development and deposition [56][57][58][59]. Therefore, the differentially expressed lncRNAs involved in the aforementioned pathways may play an important role in the process of lipid deposition and deserve further study.…”
Section: Discussionmentioning
confidence: 99%
“…9,30 In our previous studies, the roles of Lpin2/3, angiopoietin-like protein 4, miR-124-3p, and other genes and non-coding RNAs in the regulation of fat deposition from two fat-tailed sheep breeds had been discussed. [31][32][33][34] Therefore, this study mainly focuses on the crucial role of sterol regulatory element binding proteins (SREBPs) in fat-tailed sheep base on the dynamical changes of serum lipid metabolism indicators. SREBPs including SREBP-1a, SREBP-1c and SREBP2 are mainly responsible for regulating cellular lipogenesis and lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Using RNA-seq, a total of 19,878 genes were identi ed in tail fat tissues, among which 8,042 were differentially expressed between the two sheep breeds (FDR ≤ 0.001 and |Log 2 Ratio| ≥ 1). Li and co-workers reported 5,395 DEGs between tail fat tissues of Guangling large-tailed and small-tailed Han sheep [27]. In addition, 646 DEGs between Kazak and Tibetan sheep were reported by Wang et al [26], 390 DEGs between Lanzhou Fat-Tailed and Tibetan sheep by Ma et al [29] and 602 DEGs between Small-Tailed Han and Dorset sheep by Miao et al [28].…”
Section: Detection Of Variants In Candidate Genes Related To Tail-fatmentioning
confidence: 99%
“…Guangling Large-Tailed sheep and Small-Tailed Han sheep are two typical fat-tailed breeds in China. Upon application of RNA-Seq, a total of 4131 differentially expressed genes were determined in tail fat tissues of these two breeds, with FABP4, FABP5, ADIPOQ and CD36 identi ed as the four most highly transcribed genes [27]. Research on Small-Tailed Han and Dorset sheep revealed 602 differentially expressed genes, and GO analysis showed that several of these genes were enriched in the triglyceride biosynthetic process [28].…”
Section: Introductionmentioning
confidence: 99%